2009
DOI: 10.1073/pnas.0813276106
|View full text |Cite
|
Sign up to set email alerts
|

Identification of cis -regulatory sequences that activate transcription in the suspensor of plant embryos

Abstract: Little is known about the molecular mechanisms by which the embryo proper and suspensor of plant embryos activate specific gene sets shortly after fertilization. We analyzed the upstream region of the scarlet runner bean (Phaseolus coccineus) G564 gene to understand how genes are activated specifically within the suspensor during early embryo development. Previously, we showed that the G564 upstream region has a block of tandem repeats, which contain a conserved 10-bp motif (GAAAAG C /TGAA), and that deletion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
80
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(85 citation statements)
references
References 33 publications
(43 reference statements)
5
80
0
Order By: Relevance
“…Common bean has been used to characterize the molecular basis of photoperiod sensitivity and determinacy (Kwak et al, 2008). Scarlet runner bean (Phaseolus coccineus), with its very-large seeds, has been developed as a model to study embryo and seed development (Kawashima et al, 2009). The mimosoid legume Mimosa pudica (the sensitive plant), whose leaves and petioles respond to touch by closing (thigmonasty), have been studied to determine the basis for their rapid responses (Uehlein and Kaldenhoff, 2008).…”
Section: Many Models In the Legumesmentioning
confidence: 99%
“…Common bean has been used to characterize the molecular basis of photoperiod sensitivity and determinacy (Kwak et al, 2008). Scarlet runner bean (Phaseolus coccineus), with its very-large seeds, has been developed as a model to study embryo and seed development (Kawashima et al, 2009). The mimosoid legume Mimosa pudica (the sensitive plant), whose leaves and petioles respond to touch by closing (thigmonasty), have been studied to determine the basis for their rapid responses (Uehlein and Kaldenhoff, 2008).…”
Section: Many Models In the Legumesmentioning
confidence: 99%
“…Genetic studies with Arabidopsis have uncovered several genes that play major roles in seed development (9)(10)(11), including those that govern endosperm formation (12,13), embryo differentiation (14,15), and seed coat development (8). In addition, molecular studies with Arabidopsis and other plants have identified the ciscontrol regions of several genes active during seed development, particularly those encoding storage proteins, and the transcription factors (TFs) that play a role in their regulation (16)(17)(18)(19)(20)(21)(22). Nevertheless, the identities of most regulators of seed development and their direct targets are largely unknown.…”
mentioning
confidence: 99%
“…Many experimental CRM studies in plants consider cooccurrence of TFBSs of individual TFs with multiple DNA binding domains or a pair of interacting TFs (Solano et al, 1995;Chen et al, 1996;Singh, 1998;Kagaya et al, 1999;Nagano et al, 2001;Abe et al, 2003;Konishi and Yanagisawa, 2010), although a plant CRM may consist of TFBSs of three or more TFs (Baudry et al, 2004;Kim et al, 2004;Akyildiz et al, 2007;Kawashima et al, 2009;Wang et al, 2010). In addition, these studies often identify only individual CRMs for individual genes, and only consider a limited number of TFs (Steffens et al, 2005).…”
mentioning
confidence: 99%